Evaluation of the Leukemia & Lymphoma Society's Information Resource Center: A Model of Education and Support Services for Blood Cancer Patients and Their Caregivers...14th Annual Navigation & Survivorship Conference, November 15-19, 2023, San Antonio, TX. - Sheridan, Juliet D.; Sarris Esquivel, Nikie; Husick, Caroline; Sae-Hau, Maria; Yuill, Nikki; Rajotte, Michelle; Disare, Kate; Lowthert, Danielle; Weiss, Elisa (Journal of Oncology Navigation & Survivorship, 2023)
Background: The Leukemia & Lymphoma Society's (LLS) Information Resource Center's (IRC) free services are delivered by information specialists--highly trained oncology social workers and nurses who connect patients and caregivers with financial, emotional, and social support resources, and provide comprehensive disease- and treatment- related information. Objective: To assess the IRC model of education and support for blood cancer patients and their caregivers in terms of their experiences with the IRC: specifically, how well IRC services met patient/caregiver needs; the services' impact on psychosocial outcomes and health-related actions and decisions; and whether experiences varied between Spanish-speaking and English-speaking participants. Methods: A web-based survey was sent to 1711 English-speaking and 70 Spanish-speaking patients and caregivers, 18 years or older, who live in the United States and communicated with an information specialist via phone, email, or chat from September through November 2022; surveys were sent within 2 weeks of contact. All nonresponders received a follow-up email 3 days after the initial survey invitation and a final email reminder 1 week after the initial survey invitation. Spanish-speaking nonresponders also received a phone call reminder. Participants received a $20 incentive in the form of either a check or an Amazon e-gift card. A total of 614 patients and caregivers completed the evaluation survey, which represented a 34.5% overall response rate. Spanish-speaking participants had a response rate of 31.4%, were generally younger (P<.001), and were more likely to call the IRC on the phone (P<.001) compared to English-speaking participants. Results: Participants most often reported contacting the IRC because they were looking for information about how LLS could help them postdiagnosis (58.6%), with financial assistance (43.3%), and to understand the blood cancer diagnosis and treatment options (41.9%). After talking with an information specialist, respondents felt more confident managing their or their loved one's care (86.6%), more hopeful (89.2%), and less anxious (82.9%); in addition, respondents felt more knowledgeable about the blood cancer diagnosis (52.0%), financial assistance available to them (83.1%), and nutrition services (88.6%). Respondents believed the information specialists were very clear and helpful (93.9% and 93.4%, respectively), and that specialists' ability to answer questions was excellent or good (93.4%). In general, Spanish-speaking participants reported very positive experiences with the IRC information specialists, similar to English-speaking participants. A slightly higher percentage of Spanish-speaking participants said that the materials provided by LLS were only a little helpful (P=.004). Conclusion: Managing blood cancer is complex, with potentially significant financial and quality-of-life implications. The IRC provides an effective model for blood cancer patient and caregiver education, support, and assistance. This independent evaluation found that blood cancer patients and caregivers who utilize IRC services had overwhelmingly positive experiences and found the materials helpful. Respondents felt more hopeful and more confident, and they knew more about treatment options, clinical trials, and resources they could utilize. The IRC provides patients and caregivers with the resources needed to advocate for their care and supports their engagement in care delivery and decision-making.